Analisis Risiko Produk Alat Pelindung Diri (APD) Pencegah Penularan COVID-19 untuk Pekerja Informal di Indonesia - Yansen Theopilus; Thedy Yogasara; Clara Theresia; Johanna Renny Octavia (Jurnal Rekayasa Sistem Industri, 2020)
The Coronavirus Disease of 2019 (COVID-19) that is transmitted through the human respiratory system has a very high infection rate worldwide, including Indonesia. To cut off this outbreak, Indonesia has implemented some social distancing strategies that have an impact on the significant decrease of economic growth rate and the increase of poverty rate. To meet basic needs, people should continue their work in the middle of COVID-19 fear. Informal workers are among the most vulnerable groups to COVID-19 transmission because they frequently interact with the outsiders and find it difficult to comply with the health protocols. One way to prevent the COVID-19 transmission is the use of Personal Protective Equipment (PPE) such as masks, face shields, and gloves. Although these products to some degree are effective in preventing transmission, several risks that may endanger its users, such as incorrect or excessive use, incorrect maintenance, bad PPE design, and others. Therefore, this research aims to analyze the risks of the COVID-19 PPE and review the prevention recommendations for these risks. Risk analysis was carried out using the Failure Mode and Effect Analysis (FMEA) to analyze the use of masks, face shields, and gloves for the context of general informal workers in Indonesia. There are 5 aspects analyzed: product design, preparation for use, use, storage, and disposal. Based on the analysis, there are 10 mask risks, 15 face shield risks, and 12 gloves risks that need to be considered by informal workers and PPE designers and manufacturers as well.